The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/10903120802706153
|View full text |Cite
|
Sign up to set email alerts
|

Can Paramedics Read ST-segment Elevation Myocardial Infarction on Prehospital 12-Lead Electrocardiograms?

Abstract: Paramedics in an urban/suburban EMS system can diagnose STEMI and identify appropriate cardiac catheterization laboratory activations with a high degree of accuracy, and an acceptable false-positive rate, when tested using paper-based scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 24 publications
1
27
3
Order By: Relevance
“…Prehospital personnel can accurately identify ST-segment elevation from the 12-lead ECG. 47,50,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] If providers are not trained to interperet the 12-lead ECG, field transmission of the ECG or a computer report to the receiving hospital is recommended (Class I, LOE B).…”
Section: Prehospital Ecgs (Figure 1 Box 2)mentioning
confidence: 99%
“…Prehospital personnel can accurately identify ST-segment elevation from the 12-lead ECG. 47,50,[61][62][63][64][65][66][67][68][69][70][71][72][73][74] If providers are not trained to interperet the 12-lead ECG, field transmission of the ECG or a computer report to the receiving hospital is recommended (Class I, LOE B).…”
Section: Prehospital Ecgs (Figure 1 Box 2)mentioning
confidence: 99%
“…Although "false positives" are a concern when EMS personnel and/or emergency physicians are allowed to activate the cardiac catheterization laboratory, the rate of false activations is relatively low (approximately 15%) and is more than balanced by earlier treatment times for the majority of patients for whom notification is appropriate. [108][109][110][111][112][113][114] The concept of what constitutes false activation is evolving. 115,116 For patients who arrive at or are transported by EMS to a non-PCI-capable hospital, a decision about whether to transfer immediately to a PCIcapable hospital or to administer fibrinolytic therapy must be made.…”
Section: Regional Systems Of Stemi Care and Goals For Reperfusion Thementioning
confidence: 99%
“…This is consistent with the literature, which has shown that prehospital 12-lead ECG reduces door-to-balloon time by 10−55 minutes 19−24 and mortality by 7%; 24 it also suggests that prehospital ECG may either be transmitted for interpretation by hospital staff or can be interpreted locally by paramedics who then communicate their diagnosis to the hospital, with an acceptable false-positive diagnosis rate. 22,23,25,26 We speculate that the beneficial effects of recording and transmitting a 12-lead ECG in the prehospital phase of STEMI may not be restricted to patients managed with PCI; they may extend also to patients treated with thrombolysis by allowing prehospital administration and by reducing the in-hospital delay.…”
Section: Discussionmentioning
confidence: 99%